1996
DOI: 10.1046/j.1365-313x.1996.10030459.x
|View full text |Cite
|
Sign up to set email alerts
|

The CER3 gene of Arabidopsis thaliana is expressed in leaves, stems, roots, flowers and apical meristems

Abstract: The eceriferum3 (cer3) locus encodes one of 21 gene products known to be involved in wax biosynthesis in Arabidopsis thaliana. Mutations at these loci are readily identified by their bright, dark-green stems when compared with the more glaucous wild-type plant. Clones of a gene which encodes a 795 amino acid open reading frame have been isolated by using plant DNA flanking the site of a T-DNA insertion in line BRL1. Molecular complementation of the cer3 mutant phenotype by clones of this gene establish that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 0 publications
0
48
0
Order By: Relevance
“…To date, the genes corresponding to four cer mutants have been cloned from Arabidopsis: CER1 (Aarts et al, 1995), CER2 Xia et al, 1996), CER3 (Hannoufa et al, 1996), and CER6 reported here. cer1 mutants accumulate C 30 aldehyde and are deficient in C 29 alkane, secondary alcohols, and ketones (Hannoufa et al, 1993); the CER1 gene shares several characteristics with decarbonylases, indicating a role in the conversion of aldehydes to alkanes.…”
Section: Discussionmentioning
confidence: 83%
“…To date, the genes corresponding to four cer mutants have been cloned from Arabidopsis: CER1 (Aarts et al, 1995), CER2 Xia et al, 1996), CER3 (Hannoufa et al, 1996), and CER6 reported here. cer1 mutants accumulate C 30 aldehyde and are deficient in C 29 alkane, secondary alcohols, and ketones (Hannoufa et al, 1993); the CER1 gene shares several characteristics with decarbonylases, indicating a role in the conversion of aldehydes to alkanes.…”
Section: Discussionmentioning
confidence: 83%
“…For this review, we have listed 499 RING finger proteins (Supplementary Table S1), by considering, besides those collected by Stone et al [25], 27 sequences annotated as RING proteins by Kosarev et al [23] and Mladek et al [24], and three individually characterised RING proteins: CER3 [30], HOS1 (High Expression of Osmotically Responsive Gene 1) [31], and PEX12 (Peroxisomal biogenesis protein 12) [32]. These latter sequences, although not perfectly satisfying the criteria imposed by Stone et al [25], could represent potentially active E3 ubiquitin ligases.…”
Section: Ring-finger E3 Ubiquitin Ligasesmentioning
confidence: 99%
“…Four of these-CER2 , CER3 , GL2 , and GL15 -appear to encode regulatory loci (Tacke et al, 1995;Hannoufa et al, 1996;Moose and Sisco, 1996;Negruk et al, 1996;Xia et al, 1996), three-CER6 , KCS1 , and GL8 -may encode metabolic enzymes (Xu et al, 1997;Millar et al, 1999;Todd et al, 1999;Fiebig et al, 2000), and two-CER1 and GL1 -may be involved in either the transport or the metabolism of wax compounds (Aarts et al, 1995;Hansen et al, 1997). None of these genes has been associated with cuticle membrane synthesis.…”
Section: Introductionmentioning
confidence: 99%